The NleE/OspZ Family of Effector Proteins Is Required for Polymorphonuclear Transepithelial Migration, a Characteristic Shared by Enteropathogenic Escherichia coli and Shigella flexneri Infections - Zurawski, Daniel V. (American Society for Microbiology (ASM), 2008)
Enteropathogenic Escherichia coli (EPEC) and Shigella flexneri are human host-specific pathogens that infect intestinal epithelial cells. However, each bacterial species employs a different infection strategy within this environmental niche. EPEC attaches to the apical surface of small intestine enterocytes, causing microvillus effacement and rearrangement of the host cell cytoskeleton beneath adherent bacteria. In contrast, S. flexneri invades the large intestine epithelium at the basolateral membrane, replicates, and spreads cell to cell. Both EPEC and S. flexneri rely on type three secretion systems (T3SS) to secrete effectors into host cells, and both pathogens recruit polymorphonuclear leukocytes (PMNs) from the submucosa to the lumen of the intestine. In this report, we compared the virulence functions of the EPEC T3SS effector NleE and the homologous Shigella protein Orf212. We discovered that Orf212 was secreted by the S. flexneri T3SS and renamed this protein OspZ. Infection of polarized T84 intestinal epithelial cells with an ospZ deletion mutant of S. flexneri resulted in reduced PMN transepithelial migration compared to infection by the wild type. An nleE deletion mutant of EPEC showed a similar reduction of PMN migration. The ability to induce PMN migration was restored in both mutants when either ospZ or nleE was expressed from a plasmid. An infection of T84 cells with the ΔospZ mutant resulted in reduced extracellular signal-related kinase phosphorylation and NF-κB activation compared to infection with the wild type. Therefore, we conclude that OspZ and NleE have similar roles in the upstream induction of host signaling pathways required for PMN transepithelial migration in Shigella and EPEC infections.